THE MEDICAL DECISION-MAKING PROCESS AND THE FAMILY: THE CASE OF BREAST CANCER PATIENTS AND THEIR HUSBANDS - Gilbar, Roy (Bioethics, 2009)
Objectives: The objectives of the study were (1) to assess similarities and differences between breast cancer patients and their husbands in terms of doctor-patient/spouse relationships and shared decision making; and (2) to investigate the association between breast cancer patients and husbands in terms of preference of type of doctor, doctor-patient relationship, and shared decision making regarding medical treatment. Method: Fifty-seven women with breast cancer, and their husbands, completed questionnaires measuring doctor-patient/spouse relationships (paternalism, autonomy), and decision making regarding medical treatment. Results: Patients believe they have a key role in the medical decision-making process (93%) and that the participation of their husbands, and their agreement with the decision, is important (84% and 89%, respectively). Both breast cancer patients and their husbands prefer a shared decision-making process to paternalistic or autonomy-based approaches. Conclusion: In contrast to legal and bioethical approaches, which focus on the patient as the primary decision maker, this study reflects a practical recognition of the role of the breast cancer patient's husband in the decision-making process. It also reflects a relational rather than an individualistic perception of patient autonomy.